(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Because of the high standards placed on them, health professionals are often put under agreat deal of stress that may have a negative effect on their ability to provide excellent care in a varietyof challenging clinical settings. The field of sport psychology is increasingly incorporating the usage ofperformance mental skills (PMS) into its curriculum, particularly in the lead-up to and duringcompetition. The 20 studies that were reviewed all found that PMST has the potential to boostperformance, particularly in simulated environments. The major elements of the implementation were aface-to-face group lesson presented by a trainer with expertise with PMS, and the use of a multimodalapproach using a number of different PMS. 5 lessons, each lasting a mean of 57 minutes, withindividualised instructor guidance, PMS practise, and an emphasis on portability. Despite the potentialvalue of the review’s key implementation components as a guide for future PMST, further study isneeded to fill in the gaps in our understanding of the effectiveness of PMST and its primaryimplementation components, particularly in practical settings.